Nursing education - Basanvanthappa, BT (New Delhi, India : Jaypee Brothers Medical Publishers (P) Ltd., 2003)
Designed to serve as a reliable guide to the work in classroom, teaching and clinical teaching in respective are of nursing.
Introduction to nursing profession -- Concepts of education -- Philosophies of education -- Aims of education -- Functions of education -- Evolution of education in India -- Women education in India -- Professional education in India -- Curriculum concepts -- Curriculum process -- Curriculum innovation -- Coursr planning -- Teaching and the teacher -- Teaching-learning process -- Teaching strategies adn methods -- educational communication media -- Educational evaluation in nursing -- Evaluation of clinical practice in nursing -- Internal assessment -- Educational administration -- Guidance and counseling in nursing education
Includes index.
Keywords: NURSING